A 10-Year Follow-Up of Different Intra-Radicular Retainers in Teeth Restored with Zirconia Crowns [Corrigendum] - Calabro DE; Kojima AN; Gallego Arias Pecorari V; Helena Coury Saraceni C; Blatz MB; Özcan M; Mikail Melo Mesquita A (Dove Medical Press, 2020)
Calabro DE, Kojima AN, Gallego Arias Pecorari V, et al. Clin Cosmet Invest Dent. 2019;11: 409–417. The authors of this paper have advised that the affiliations are incorrect. The correct author list and affiliations are as follows: Debora E Calabro,1 Alberto N Kojima,2 Vanessa Gallego Arias Pecorari,3 Cintia Helena Coury Saraceni,3 Markus B Blatz,4 Mutlu Özcan,5 Alfredo Mikail Melo Mesquita1 1Department of Prosthodontics, Paulista University (UNIP) São Paulo, São Paulo, Brazil; 2Department of Dental Materials and Prosthodontics, Paulista State University (UNESP) São José, São Paulo, Brazil; 3Department of Dental Materials, Paulista University (UNIP), São Paulo, Brazil; 4Department of Preventive and Restorative Sciences, University of Pennsylvania,Philadelphia, PA, USA; 5Division of Dental Materials, Clinic for Reconstructive Dentistry, University of Zurich, Zurich, Switzerland Read the original article